Autocrítica autoetnográfica como alternativa ontoepistêmica: uma tese-diálogo tecida na heterogeneidade - Camila Oliveira Fonseca (2023)
The main goal of this study is to trigger a pragmatic shift that aims to denaturalize the contextual character of the interpretative processes through which this academic-scientific research is constituted. Situated within the field of Applied Linguistics and precisely because of the questioning and problematizing impulse that sustains it, this research consolidates as a self-critical exercise that provokes a continuous and persistent movement of interrupting the stability that intends to confine the body-mind-spirit complexity manifested throughout this study. Having as a starting point the paradigm of situated heterogeneity, the memories and narratives of personal experiences shared in this work interact with different perspectives and cosmovisions, in addition to establishing a constant dialogue with the reader. Various forms of expression and language favor the situated heterogeneity that unfolds throughout the text, bringing to the fore conflicts and questions that serve as fuel for dialogue. The performative decolonial praxis that unfolds in this work offers contributions to the extent that it interrupts the logic of separability that puts meanings which are mutually constituted in opposition and makes evident the incompleteness and interdependence that make possible the dialogue between the different and among the differences that constitute the heterogeneity of beings and knowledge, helping to preserve the dissent that ensures coexistence.